TYPES, CAUSES AND TREATMENT OF MENINGITIS. - Tulaganova Nigora (Prospects for innovative technologies in science and education, 2025)
Meningitis is an infectious disease that occurs as a result of inflammation of the membranes surrounding the brain and spinal cord (meninges). This condition represents a serious health problem that requires emergency medical attention. Meningitis can be bacterial, viral or fungal, and its symptoms can vary from person to person. This article will explain in detail what meningitis is, its symptoms, causes and treatment methods.